Candidate Effector Pst_8713 Impairs the Plant Immunity and Contributes to Virulence of Puccinia striiformis f. sp. tritici - Zhao, Mengxin; Wang, Jianfeng; Ji, Sen; Chen, Zengju; Xu, Jinghua; Tang, Chunlei; Chen, Shuntao; Kang, Zhensheng; Wang, Xiaojie (Frontiers in Plant Science, 2018)
Puccinia striiformis f. sp. tritici (Pst), the causal agent of stripe rust, is an obligate biotrophic pathogen responsible for severe wheat disease epidemics worldwide. Pst and other rust fungi are acknowledged to deliver many effector proteins to the host, but little is known about the effectors’ functions. Here, we report a candidate effector Pst_8713 isolated based on the genome data of CY32 and the expression of Pst_8713 is highly induced during the early infection stage. The Pst_8713 gene shows a low level of intra-species polymorphism. It has a functional N-terminal signal peptide and its product was found in the host cytoplasm and nucleus. Co-infiltrations in Nicotiana benthamiana demonsrated that Pst_8713 was capable of suppressing cell death triggered by mouse pro-apoptotic protein-BAX or Phytophthora infestans PAMP-INF1. Overexpression of Pst_8713 in plants suppressed pattern-triggered immunity (PTI) -associated callose deposition and expression of PTI-associated marker genes and promoted bacterial growth in planta. Effector-triggered immunity (ETI) induced by an avirulent Pst isolate was weakened when we overexpressed Pst_8713 in wheat leaves which accompanied by reduction of reactive oxygen species (ROS) accumulation and hypersensitive response (HR). In addition, the host induced gene silencing (HIGS) experiment showed that knockdown of Pst_8713 weakened the virulence of Pst by producing fewer uredinia. These results indicated that candidate effector Pst_8713 is involved in plant defense suppression and contributes to enhancing the Pst virulence.